PEMILIHAN PEMASOK NATA DE COCO DENGAN METODE ANALYTIC HIERARCHY PROCESS (STUDI KASUS UMKM ES BUAH PRASMANAN ARUMI) BERAU, KALIMANTAN TIMUR - Hasto Wisnugroho, Anthonius Dhinar (Jurnal Inkofar, 2023)
Supplier performance appraisal is an important decision in a company, because it will increase the company's competitiveness in the face of very competitive business competition. UMKM Ice Fruit Buffet Arumi is currently selecting suppliers who will supply raw materials for Nata de Coco with three suppliers, namely Solo Swalayan, Nano Mart, and Toko Idang. In the selection of suppliers carried out by the Arumi Fruit Ice Cream UMKM, previously it was only based on the intuition of the business owner and there were no previous methods that supported it. The method used in this study is the Analytical Hierarchy Process (AHP). The criteria that can be used to assess supplier performance are price, quality, and location. The research location was carried out at an Arumi Fruit Ice Cream UMKM located on Jl. Mount Panjang, Tanjung Redeb, Berau. Respondents in this study were the owners of UMKM Ice Fruit Arumi Buffet. The results showed that the highest score was "Solo Supermarket" with a value of 0.563236, then "Nano Mart" with a value of 0.2155, and the last was "Toko Idang" with a value of 0.2212528. So it was concluded that the best supplier was "Self Service Solo".